ڕۆڵی لێژنەی ئاشتەوایی لە گونجاندنەوەی خێزاندا توێژینەوەیەكی مەیدانیە لە ناو شاری سلێمانی توێژینەوەیەكی هەڵێنجراو لە نامەی ماستەر - فرج, نجاە محمد; احمد, بەسۆز عبدالرحیم (Sulaimani Journal for Humanities, 2022)
This study talks about the role of the compatibility committee in family guidance and compatibility. In this study, we talk a lot about this committee, because this committee is fairly recent. It was created by the Domestic Violence Court in Sulaymaniyah and other regions (Erbil, Dohuk, Halabja, Garmian, Soran and Raparin) in (2012), and one of the objectives of this study is to uncover the reasons for the creation of this committee. Then he talked about the statistics (2018-2020) that have been presented by this committee, and this study also tries to present the difficulties and the consensus which hampers the work of this committee in the family agrees. That this study, a study of the field used the descriptive approach and social survey, and the study sample is not random, including committee members and administrators. Their structure is less than the number of those who disagree because there are barriers to the work of this committee, for example, the imbalance between the skills of this committee, as a legal, social and psychological specialist.